The Level of Student Learning Motivation in Physical Education Learning From a Gender Perspective at SMA Negeri 1 Bengkalis: Tingkat Motivasi Belajar Siswa Pada Pembelajaran Pendidikan Jasmani Dilihat Dari Segi Gender Di SMA Negeri 1 Bengkalis - Sri Mahyuni; M. Fransazeli Makorohim (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Physical Education is part of the overall education that prioritizes physical activity and fostering a healthy life for harmonious, harmonious and balanced physical, mental, social and emotional growth and development. Learning models were created by considering several factors, namely: (1) subject characteristics. (2) teacher's ability. (3) The characteristics of children are divided into two characteristics of boys and characteristics of girls. The purpose of this study was to determine the level of student learning motivation in physical learning in terms of gender at high school Negeri Negeri 1 Bengkalis. This type of research is quantitative descriptive research. In this study, the population consisted of all students of SMA Negeri 1 Bengkalis, totaling 694 students. From the large population, the researchers took a sample of 50 students, consisting of 25 boys and 25 girls with the research technique is random sampling. The research instrument used was a questionnaire. Based on the results of the research, the conclusions obtained in this study are as follows : The level of students' learning motivation in physical education learning in terms of gender at senior high school Negeri 1 Bengkalis is 63% of male students who are classified as "Good enough" and 62% of female students who are classified as "Good enough".